Considerations on the control design for a three-tether wave energy converter. (1st July 2019) - Sergiienko, N.Y.; Cazzolato, B.S.; Arjomandi, M.; Ding, B.; da Silva, L.S.P.
Abstract: Wave energy converters (WECs) capable of extracting power in multiple degrees of freedom require a special attention from control engineers as the control problem becomes multivariable involving highly coupled dynamics of the plant. Taking the three-tether submerged buoy as an example of a multi-degree-of-freedom WEC, this paper presents three main steps that should be taken during control system development. Firstly, an understanding of the system dynamics, its rigid body modes of vibration and input/output controllability is built using the singular value decomposition approach. Then, a causal close-to-optimal controller developed for the single-tether heaving WEC is extended to the multivariable control problem, demonstrating a significant increase in the power output as compared to the simple spring-damper approach. At the final stage, technical requirements imposed by this controller on the power take-off (PTO) machinery are investigated showing that, in order to achieve a 15%-improvement in power absorption compared to a quasi-standard spring-damper control, the amount of reactive power should be increased by 50%, forcing one PTO unit to operate as an actuator all the time.